Bone morphogenetic protein signaling in vertebrate motor neurons and neuromuscular communication - Osses, Nelson; Henríquez, Juan P. (Frontiers in Cellular Neuroscience, 2015)
An accurate communication between motor neurons and skeletal muscle fibers is required for the proper assembly, growth and maintenance of neuromuscular junctions (NMJ). Several signaling and extracellular matrix molecules play stimulatory and inhibitory roles on the assembly of functional synapses. Studies in Drosophila have revealed crucial functions for early morphogens, such as members of the Wnt and Bone Morphogenetic Proteins (BMP) signaling pathways, during the assembly and maturation of the NMJ. Here, we bring together recent findings that led us to propose that BMPs also work in vertebrate organisms as diffusible cues to communicate motor neurons and skeletal muscles.